IMMUNIZATION OF CHILDREN AGAINST PNEUMOCOCCAL DISEASE: PRACTICAL ASPECTS FROM THE STANDPOINT OF AN OTOLARYNGOLOGIST - S. G. Gubanova; А. K. Gevorkyan; Yu. V. Rovenskaya (Вопросы современной педиатрии)
The article describes the results of studying the effectiveness of vaccination of children with allergic disorders and frequently ill children against pneumococcal diseases. The effectiveness and good tolerability of the vaccine was detected. A follow-up study of the vaccinated children was performed. The positive effect of vaccination on the incidence of acute respiratory diseases, acute adenoiditis and acute otitis media in all groups of children was shown. The positive effect of vaccination on the degree of hyperplasia of adenoid tissue in the nasopharynx of frequently ill children was proved.